Identifikasi Air Tanah Menggunakan Electrical Resistivity Tomography di Lingkungan Sekolah Rakyat Menengan Atas 40 Ambon - Latuconsina, Usman Aria Ramadhan; Kaharudin, Husnaniah; Sukri, Muh. Riswan Anas (Tanah Goyang : Jurnal Geosains, 2025)
Clean water availability is a vital requirement for supporting learning activities and maintaining health within educational environments. Sekolah Rakyat Ambon, located in Maluku, still experiences limited access to clean water due to complex local geological conditions and the absence of a well-identified groundwater system. This study aims to identify potential aquifer zones around Sekolah Rakyat Ambon using the 2D Electrical Resistivity Tomography (ERT) method as a basis for groundwater drilling site selection. The survey was conducted along a 156-meter line with a 4-meter electrode spacing using the Wenner-Schlumberger configuration. The inversion results reveal a low-resistivity zone (10–50 Ωm) at a depth of approximately 25–30 meters, interpreted as a saturated aquifer layer. Based on this interpretation, drilling was carried to a depth of 30 meters. Borehole observations confirmed the presence of water-bearing sandy layers consistent with the ERT results. Physical water quality testing yielded values of pH 8.20, EC 273 µS/cm, TDS 146 ppm, salinity 0.001%, and specific gravity 1 g/cm³, indicating that the water is suitable for clean water use. The discharge measurement resulted in a flow rate of approximately 25 liters per minute, sufficient to meet the school’s daily water needs.